Racial Differences in Patient Portal Activation and Research Enrollment Among Patients With Prostate Cancer. (2021) - Halbert, Chanita Hughes; Jefferson, Melanie; Allen, Caitlin G.; Babatunde, Oluwole A.; Drake, Richard; Angel, Peggi; Savage, Stephen J.; Frey, Lewis; Lilly, Michael; Obi, Ted; Obeid, Jihad
Abstract : PURPOSE: The purpose of this study was to examine racial differences in patient portal activation and research participation among patients with prostate cancer. MATERIALS AND METHODS: Participants were African American and White patients with prostate cancer who were treated with radical prostatectomy (n = 218). Patient portal activation was determined using electronic health records, and research participation was measured based on completion of a social determinants survey. RESULTS: Thirty-one percent of patients completed the social determinants survey and enrolled in the study and 66% activated a patient portal. The likelihood of enrolling in the study was reduced with greater levels of social deprivation (odds ratio [OR], 0.70; 95% CI, 0.50 to 0.98; P = .04). Social deprivation also had a signification independent association with patient portal activation along with racial background. African American patients (OR, 0.48; 95% CI, 0.23 to 0.91; P = .02) and those with greater social deprivation (OR, 0.58; 95% CI, 0.42 to 0.82; P = .002) had a lower likelihood of activating a patient portal compared with White patients and those with lower social deprivation. CONCLUSION: Although the majority of patients with prostate cancer activated their patient portal, rates of patient portal activation were lower among African American patients and those who lived in areas with greater social deprivation. Greater efforts are needed to promote patient portal activation among African American patients with prostate cancer and address access to health information technology among those who live in socially disadvantaged geographic areas.